2002
DOI: 10.1016/s0375-9474(02)00919-3
|View full text |Cite
|
Sign up to set email alerts
|

Probing hadronic formation times with antiprotons in p+A reactions at AGS energies

Abstract: The production of antiprotons in p + A reactions is calculated in a microscopic transport approach employing hadronic and string degrees of freedom (HSD). It is found that the abundancies of antiprotons as observed by the E910 Collaboration in p + A reactions at 12.3 GeV/c as well as 17.5 GeV/c can approximately be described on the basis of primary proton-nucleon and secondary meson-baryon production channels for all targets. The transport calculations demonstrate that the antiproton rapidity distributions for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
7
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
5
7
0
Order By: Relevance
“…The data for N and Kr could then be well described using a formation time τ f > 0.3fm/c for all hadrons. This value is compatible with the analysis of antiproton attenuation in p + A reactions at AGS energies [15].…”
supporting
confidence: 90%
“…The data for N and Kr could then be well described using a formation time τ f > 0.3fm/c for all hadrons. This value is compatible with the analysis of antiproton attenuation in p + A reactions at AGS energies [15].…”
supporting
confidence: 90%
“…[39,40] have demonstrated that the dominant final state interactions of the hadrons with maximum momentum, as measured by the HERMES collaboration [42], are compatible to the concepts described above. This also holds for antiproton production and attenuation in proton-nucleus collisions at AGS energies [56].…”
Section: Perturbative Treatment Of High P ⊥ Hadrons and Jetsmentioning
confidence: 79%
“…This finding is remarkable, since the same dynamics also describe the hadron formation and attenuation in deep-inelastic lepton scattering off nuclei at HERMES [43] quite well. Additionally, this also holds for antiproton production and attenuation in proton-nucleus collisions at AGS energies [45].…”
Section: Discussionmentioning
confidence: 94%